Phytochemical Screening And Antibacterial Activity Of The Ethanol Extract Of Putri Malu (Mimosa Pudica Linn.) Leaves Combined With Klanceng Honey Against Staphylococcus Aureus Bacteria - Dalimunte, Khairunnisa; Arianto, Anayanti; Salim, Emil (Publisher Cv. Inara, 2023)
Mimosa pudica Linn. Leave and honey have been known to have antibacterial activity. The combination of the two is very beneficial as an antibacterial because the hydrogen peroxide content in honey and the flavonoid metabolite compounds in Putri Malu provide a synergistic effect as an antibacterial. The aim of this research was to determine the activity of the ethanol extract of Putri Malu leaves combined with Klanceng honey using the disc diffusion method against Staphylococcus aureus bacteria. The results showed that the resulting extract was thick and blackish-green in colour, with a yield of 25.6%. The results of the phytochemical screening test showed that Putri Malu extract contains alkaloids, flavonoids, glycosides, saponins, and tannins. Characterization results showed that the water content of the extract was 7.28 ± 0.05, water-soluble essence content was 16.03 ± 0.08, ethanol-soluble essence content was 19.65 ± 0.01, total ash content was 4.70 ± 0.00, and essence content acid soluble was 0.17±0.02. Antibacterial testing showed that the best ratio of Putri Malu leaf extract to honey to inhibit Staphylococcus aureus was 9:1, with an inhibitory value of 13.60 ± 0.40 mm. In conclusion, the combination of Putri Malu leaf extract with honey strongly inhibits the growth of Staphylococcus aureus bacteria.